Bosnia and Herzegovina : Assessment of MFd's Technical Assistance Program. (Policy Papers; Policy Paper ;, 2006)
This report summarizes the findings of an evaluation of the technical assistance delivered by MFD to the CBBH. The assessment was conducted during a visit to Bosnia and Herzegovina during the period March 15-17, 2006. It covers the period 1997-2005, although MFD TA started earlier: two brief MFD staff visits took place in 1996 to assist the authorities in preparing legislation to establish a currency board and create a market-based central bank.